Effect of Al2O3 content on the high-temperature oxidation behaviour of CoCrAlYTa coatings produced by laser-induction hybrid cladding. (December 2022) - Qin, Lei; Ren, Pan; Yi, Yanliang; Xie, Tianjin; Hu, Yunlong; Chen, Dongchu; Zhou, Shengfeng
Abstract: The microstructure and isothermal oxidation behaviour of CoCrAlYTa coatings containing different Al2 O3 contents produced by laser-induced hybrid cladding (LIHC) were investigated. The results showed that the addition of Al2 O3 particles to the CoCrAlYTa coatings reduced the critical concentration of Al due to the increased diffusion coefficient of Al, which promoted the formation of continuous and complete Al2 O3 scales. However, the growth of tantalum oxide in the CoCrAlYTa coating resulted in cracking of the surrounding oxide scales. Interestingly, a CoCrAlYTa coating made of the optimal content of 2 wt% Al2 O3 formed an oxide scale with good compactness after high-temperature oxidation. Highlights: CoCrAlYTa coatings are produced by laser-induction hybrid cladding (LIHC). Adding alumina particles can promote the formation of a continuous and intact Al2 O3 scale. The optimal addition amount of alumina particles is 2 wt% in this work. The growth of tantalum oxide can cause cracking of the surrounding scales.